Designing halfring artificial magnetic conductor for RFID application - Abu, Maisarah; Hussin, Eryana Eiyda; Zakaria, Zahriladha; Mohamad Isa, Mohd Sa'ari; Baharudin, Zikri Abadi (2013)
This paper proposed and discussed the new structure of halfring AMC for RFID application. The use of AMC is designed to overcome the problem of cancellation of the image current by redirecting back the electromagnetic wave reflected by the metal plate. Low profile dipole antenna is used to represent the RFID transponder. Three size of optimized AMC is presented to study the characteristics of the halfring AMC. The best result obtained by implementing the optimized halfring in lamda,λ and half-lamda, 1/2λ size. The gain is higher than 7dB with return loss of -16dB proved that this structure can be used onto the RFID technology system for metal or non-metal object.